Perancangan Sistem Informasi Akuntansi Pada UMKM Toko 168 - Serly Serly; Mery Susanti (Universitas Internasional Batam, 2021)
The activity was intended to give the solution for accounting problems experienced by client. Toko 168 was a kind of business sold items that Chinese ethnic needs in prayer ritual. So far, Toko 168 has only recorded the cash transaction and has not been done the stock opname for a long time. It’s caused the owner couldn’t find out the profit or loss of business. Furthermore, without the stock opname action potentially raised the risk of stock loss and damage. Methods used in this activity were simulation and user training with the accounting information system created by Microsoft Access. Writer collected the business information through interviews, observation, and historical documents. The outputs from activity were a computerized accounting system, financial statements at the end of period, and user manual. After implementation, the results obtained were client get the profit or loss of business clearly and easily. Besides as for checking the loss and damage stock, stock opname routine also reminded client to fill stock before it runs out. The system currently designed only supports use on Windows. Following the technology development, the next PkM recommended to improve the system to the application version and can be operated on android. In the future, it is also expected to add a tax system function.